O Direito constitucional à saúde e o sistema de saúde complementar - Suryan, Jaqueline (2014)
This is a study of a review of the constitutional right to health care and its impacts on the Complementary Health System provided for by the Brazilian Federal Constitution of 1988. From a study of the historical background of fundamental rights and the evolution of social rights as positive actions by the State, we can verify the importance given to these rights throughout the centuries. From this scenario of evolution of rights worldwide, it is relevant a historical and evolutional review of the constitutional right to health care within the Brazilian constitutional system, showing the passage of a legislative and constitutional gap of protection of the right to health care until the comprehensive and universal protection of this right, as established in Sections 6 and 196 of the Brazilian Federal Constitution of 1988. A study on the Social Security System and the constitutional principles inherent to it serves as a basis for structuring the Complementary Health System innovated by the Federal Constitution of 1988. The international protection of the constitutional right to health care was reviewed through study of Comparative Law, based on the constitutions of the American and European states and Public International Law, as well as international and specific doctrines on this regard. Once examined the origin and importance of the constitutional right to health care, nationally and internationally, an analysis was made of the Complementary Health System, through the verification of a positivistic validity of its main rules, such as the Law No. 9,656, of June 3, 1998, which regulates the of Complementary Health System at a federal level, and the Law No. 9,961, of January 28, 2000, that creates the state s sector regulatory agency, as well as the enforcement of the constitutional right to health care by means of the state provisions of healthcare services and the impact of this fundamental right in private actions related to complementary health. Finally, some of the main provisions of Law no. 9,661/1998 were reviewed in order to study the social impacts and liberty of the performance of services by the private initiative related to complementary healthcare, without shackling or reducing the right of health care as established in the Brazilian Federal Constitution of 1988